Preparation method and application of ETS-10 zeolite with nanocrystal stacking morphology

CN118637636BActive Publication Date: 2026-10-16CHANGZHOU INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410510307.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-26
Publication Date
2026-10-16
Estimated Expiration
2044-04-26

AI Technical Summary

Technical Problem

[0004]为了解决ETS-10沸石在生产过程中无法同时兼顾获得较好孔结构与形貌、高结晶度及低成本的技术问题,本发明提供一种具有纳米晶堆积形貌的ETS-10沸石的制备方法及应用

Benefits of technology

[0021] This invention utilizes water glass as the silicon source, titanium trichloride as the titanium source, and citric acid as an additive to directly synthesize hierarchical porous ETS-10 zeolite molecular sieves with nanocrystalline stacking morphology via hydrothermal crystallization. During the synthesis process, citric acid acts as a pore-forming agent, morphology regulator, and structure-directing agent. Under alkaline conditions, the titanium and silicon sources exist as TiO2(OH)- and SiO2(OH)-, respectively, combining to form the basic units for molecular sieve growth and continuing to stack to form more secondary units such as amorphous particles or nanocrystals. These secondary units facilitate rapid nucleus generation and self-assemble under van der Waals forces. The resulting product ultimately exhibits a bipyramidal structure with typical ETS-10 characteristics formed by nanocrystalline stacking. The nanocrystalline stacking process promotes rapid nucleus generation, significantly increasing the crystal growth rate and reducing the synthesis time and cost of ETS-10 zeolite. Compared with existing technologies, this method greatly shortens the crystallization time, reduces the dependence on mesoporous organic templates in traditional synthesis methods, and provides a simple and environmentally friendly synthetic route.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118637636B_ABST
    Figure CN118637636B_ABST
Patent Text Reader

Abstract

The application relates to a preparation method and application of ETS-10 zeolite with a nanocrystal accumulation morphology, and comprises the following steps: uniformly mixing organic acid and a titanium source to form a solution A; adding a sodium hydroxide solution into a water glass and uniformly stirring to obtain a solution B; adding the solution A into the solution B, adding a potassium fluoride solution to adjust the pH value of the system, or adding the potassium fluoride solution into the solution B to adjust the pH value of the system, then adding the solution A, continuously stirring, carrying out a hydrothermal crystallization reaction at 230 DEG C for more than 6 hours, taking out a product, washing and drying, and carrying out calcination at 450 DEG C for 5 hours to obtain the product; wherein the organic acid has at least two carboxyl groups and at least one hydroxyl group; the application reduces the crystallization time, and ETS-10 zeolite molecular sieve with a nanocrystal accumulation special morphology and a hierarchical pore structure is obtained, and the catalyst prepared from the ETS-10 zeolite molecular sieve has high catalytic activity and thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of zeolite molecular sieve technology, specifically to a method for preparing and applying ETS-10 zeolite with a nanocrystalline morphology. Background Technology

[0002] Microporous zeolites, due to their uniform pore structure, high thermal and hydrothermal stability, large surface area, and cation exchangeability, are widely used in industrial fields such as ion exchange, adsorption and separation, industrial catalysis, and host-guest chemistry. Microporous ETS-10 zeolite molecular sieve is a titanium-silicon molecular sieve with a unique microporous structure. Its framework of silicon-oxygen tetrahedra and titanium-oxygen octahedra is connected by oxygen bridges, forming a multidimensional structure of twelve-membered, seven-membered, and five-membered rings. This zeolite is widely used as a heterogeneous catalyst in many catalytic fields such as the photodegradation of large aromatic compounds, photocatalysis, hydrogenation conversion, and biomass conversion. However, the small pore size of microporous ETS-10 zeolite is not conducive to molecular diffusion, severely limiting its mass transfer capacity. Furthermore, the synthesis process of ETS-10 zeolite requires approximately 72 hours of crystallization time, which reduces synthesis efficiency and limits its industrialization. Therefore, introducing mesoporous structures into microporous zeolites facilitates the diffusion of reactant molecules and enables the catalytic transformation of macromolecules. At the same time, shortening the synthesis time will further expand the wide application of zeolite catalytic materials in petroleum refining, petrochemicals, and fine chemicals.

[0003] The introduction of mesopores into ETS-10 zeolite was initially achieved through acid-base treatment or microwave radiation treatment. However, these methods resulted in a limited number of mesopores and also damaged the zeolite's structure. While using long-chain aminosilanes as soft templates can successfully prepare hierarchically porous ETS-10 zeolite molecular sieves with complete structures, organic templates are expensive, prone to pollution, and unsuitable for large-scale production. Recently, additives such as sodium lignosulfonate and metal nitrates have been used to successfully synthesize hierarchically porous ETS-10 zeolite molecular sieves with special morphologies, achieving effective control over pore structure and morphology. However, the use of sodium lignosulfonate leads to a significant decrease in zeolite crystallinity, and metal nitrates are expensive additives. Summary of the Invention

[0004] To address the technical challenge of simultaneously achieving good pore structure and morphology, high crystallinity, and low cost in the production of ETS-10 zeolite, this invention provides a method for preparing and applying ETS-10 zeolite with a nanocrystalline stacked morphology. This invention reduces crystallization time while yielding an ETS-10 zeolite molecular sieve with a unique nanocrystalline stacked morphology and a hierarchical porous structure. Using the ETS-10 zeolite molecular sieve with its unique nanocrystalline stacked morphology and hierarchical porous structure obtained by this invention as a catalyst support for a transition metal catalyst, it exhibits high catalytic activity and thermal stability in the CO2 carbonylation of glycerol reaction.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solution:

[0006] The first aspect of this invention provides a method for preparing ETS-10 zeolite with a nanocrystalline stacking morphology, comprising the following steps:

[0007] Solution A is obtained by separately forming solutions of organic acid and titanium source and then mixing them evenly.

[0008] Sodium hydroxide solution was added to water glass and stirred until homogeneous to obtain solution B.

[0009] Solution A was added dropwise to solution B, and then potassium fluoride solution was added to adjust the pH of the system to 11-11.5. Alternatively, potassium fluoride solution was added dropwise to solution B to adjust the pH of the system to 11-11.5 before adding solution A. The mixture was stirred continuously and subjected to a hydrothermal crystallization reaction at 230°C for more than 6 hours. The product was then removed, washed, dried, and calcined at 450°C for 5 hours to obtain ETS-10 zeolite with a nanocrystalline morphology.

[0010] The organic acid has at least two carboxyl groups and at least one hydroxyl group;

[0011] The raw materials are added according to the following molar ratio: SiO2:TiO2:K2O:Na2O:organic acid:H2O = 6.2:1.0:1.8:4.5:(0.5-0.8):(160-210).

[0012] Furthermore, the organic acid is citric acid (AC), the silicon source is water glass, and the titanium source is titanium trichloride.

[0013] Furthermore, the raw materials are added according to the following molar ratio: SiO2:TiO2:K2O:Na2O:organic acid:H2O = 6.2:1.0:1.8:4.5:(0.5-0.8):(185-200).

[0014] Preferably, the raw materials are added according to the following molar ratio: SiO2:TiO2:K2O:Na2O:organic acid:H2O = 6.2:1.0:1.8:4.5:(0.6-0.8):185.

[0015] Furthermore, the hydrothermal crystallization time is 24-72 hours.

[0016] Preferably, the hydrothermal crystallization time is 48-72 hours, which can make the crystallinity reach more than 90% and have a nanocrystal stacking morphology.

[0017] Furthermore, the system should be stirred for 1-3 hours before adding the potassium fluoride solution and after adjusting the pH to the desired value.

[0018] The second aspect of the present invention provides the application of ETS-10 zeolite with nanocrystalline stacking morphology obtained by the above preparation method in the catalytic CO2 carbonylation of alcohols reaction, wherein ETS-10 zeolite with nanocrystalline stacking morphology is used as a support to block transition metals to form a catalyst.

[0019] Furthermore, the transition metal is one or more of zinc, cobalt, nickel, cerium, and zirconium.

[0020] Beneficial technical effects:

[0021] This invention utilizes water glass as the silicon source, titanium trichloride as the titanium source, and citric acid as an additive to directly synthesize hierarchical porous ETS-10 zeolite molecular sieves with nanocrystalline stacking morphology via hydrothermal crystallization. During the synthesis process, citric acid acts as a pore-forming agent, morphology regulator, and structure-directing agent. Under alkaline conditions, the titanium and silicon sources exist as TiO2(OH)- and SiO2(OH)-, respectively, combining to form the basic units for molecular sieve growth and continuing to stack to form more secondary units such as amorphous particles or nanocrystals. These secondary units facilitate rapid nucleus generation and self-assemble under van der Waals forces. The resulting product ultimately exhibits a bipyramidal structure with typical ETS-10 characteristics formed by nanocrystalline stacking. The nanocrystalline stacking process promotes rapid nucleus generation, significantly increasing the crystal growth rate and reducing the synthesis time and cost of ETS-10 zeolite. Compared with existing technologies, this method greatly shortens the crystallization time, reduces the dependence on mesoporous organic templates in traditional synthesis methods, and provides a simple and environmentally friendly synthetic route. Attached Figure Description

[0022] Figure 1The XRD patterns of hierarchical porous ETS-10 zeolite molecular sieves synthesized with different amounts of citric acid in Examples 1-4 are shown; where a represents AC:TiO2 = 0.2, b represents AC:TiO2 = 0.4, c represents AC:TiO2 = 0.6, and d represents AC:TiO2 = 0.8; the above ratios are molar ratios.

[0023] Figure 2 The XRD patterns of the hierarchical porous ETS-10 zeolite molecular sieves synthesized by different citric acid addition methods in Examples 3 and 5 are shown; where a represents the direct addition of solid citric acid and b represents the addition of citric acid solution.

[0024] Figure 3 The XRD patterns of hierarchical porous ETS-10 zeolite molecular sieves synthesized in Examples 3 and 6-9 with different water-to-titanium ratios are shown; where a represents H2O:TiO2 = 150, b represents H2O:TiO2 = 170, c represents H2O:TiO2 = 185, d represents H2O:TiO2 = 200, and e represents H2O:TiO2 = 210; the above ratios are molar ratios.

[0025] Figure 4 The XRD patterns of multi-level porous ETS-10 zeolite molecular sieves synthesized in different material addition sequences in Examples 3, 10, and 11 are shown; where a represents Example 11, b represents Example 10, and c represents Example 3.

[0026] Figure 5 The XRD patterns are of hierarchical porous ETS-10 zeolite molecular sieves synthesized at different crystallization times in Examples 3, 12-15 and Comparative Example 1; where a represents t=48h in Comparative Example 1, b represents t=6h, c represents t=12h, d represents t=24h, e represents t=48h, and f represents t=72h.

[0027] Figure 6 The image is a scanning electron microscope (SEM) image of the sample with a typical ETS-10 truncated biconical morphology obtained in Example 11.

[0028] Figure 7 and Figure 8 This is a scanning electron microscope (SEM) image of the sample with nanocrystalline stacking morphology obtained in Example 10.

[0029] Figure 9 The adsorption isotherm and pore distribution curve are from Example 12. Detailed Implementation

[0030] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0031] Unless otherwise specifically stated, the numerical values ​​set forth in these embodiments do not limit the scope of the invention. Techniques and methods known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques and methods should be considered part of the specification. In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not as limitations. Therefore, other examples of exemplary embodiments may have different values.

[0032] Experimental methods not specified in the following examples are generally performed according to national standards; if there is no corresponding national standard, they are performed according to general standard requirements or general methods.

[0033] In the following examples and comparative examples, the molar ratios of each material, such as "SiO2:TiO2:K2O:Na2O:H2O", refer to the following: SiO2 refers to the silicon source, and the number of moles of the silicon source is the number of moles of silicon in the water glass; TiO2 refers to the titanium source, and the number of moles of the titanium source is the number of moles of titanium in the titanium trichloride hydrochloric acid solution (15-20 wt.%); K2O refers to the number of moles of potassium in potassium fluoride; Na2O refers to the sum of the number of moles of sodium in the water glass and sodium hydroxide in the system; and H2O refers to the total number of moles of water used in the system.

[0034] Water glass contains 6.865 mol / L SiO2, 1.8444 mol / L Na2O, and 49.8333 mol / L H2O.

[0035] Crystallinity (%) testing and calculation method: Crystallinity was tested using an X-ray diffractometer, and the calculation formula was: Crystallinity = (Diffraction peak intensity / Total intensity) * 100%. Data processing was performed using Jade software.

[0036] The specific surface area was measured using a physical adsorption analyzer.

[0037] SEM images were obtained using an emission scanning electron microscope.

[0038] Example 1

[0039] In this case, the raw materials were added according to the following molar ratio: SiO2:TiO2:K2O:Na2O:AC:H2O = 6.2:1.0:1.8:4.5:0.2:185.

[0040] Solution A: Prepared by adding 3 mL of 0.76 mol / L citric acid solution dropwise to 10 mL of TiCl3;

[0041] Solution B: Measure 10 mL of 5.84 mol / L sodium hydroxide solution and add it dropwise to water glass, stirring for 1 h.

[0042] Solution A was added dropwise to solution B and stirred for 2 hours. Finally, 11 mL of 2.92 mol / L potassium fluoride solution was added to adjust the pH to approximately 11.2. After stirring for 1 hour, a hydrothermal crystallization reaction was carried out at 230℃ for 72 hours. The product was removed, washed, dried, and calcined at 450℃ for 5 hours to obtain hierarchical porous ETS-10 zeolite. SEM observation showed that the product morphology was a typical truncated bipyramidal morphology of ETS-10.

[0043] Example 2

[0044] In this case, the raw materials were added according to the following molar ratio: SiO2:TiO2:K2O:Na2O:AC:H2O = 6.2:1.0:1.8:4.5:0.4:185.

[0045] Solution A: Prepared by adding 4 mL of 1.13 mol / L citric acid solution dropwise to 10 mL of TiCl3;

[0046] Solution B: Measure 10 mL of 5.84 mol / L sodium hydroxide solution and add it dropwise to water glass, stirring for 1 h;

[0047] Solution A was added dropwise to solution B and stirred for 2 hours. Finally, 11 mL of 2.92 mol / L potassium fluoride solution was added to adjust the pH to approximately 11.2. After stirring for 1 hour, a hydrothermal crystallization reaction was carried out at 230℃ for 72 hours. The product was removed, washed, dried, and calcined at 450℃ for 5 hours to obtain hierarchical porous ETS-10 zeolite. SEM observation showed that the product morphology was a typical truncated bipyramidal morphology of ETS-10.

[0048] Example 3

[0049] In this case, the raw materials were added according to the following molar ratio: SiO2:TiO2:K2O:Na2O:AC:H2O = 6.2:1.0:1.8:4.5:0.6:185.

[0050] Solution A: Prepared by adding 5 mL of 1.36 mol / L citric acid solution dropwise to 10 mL of TiCl3;

[0051] Solution B: Measure 10 mL of 2.43 mol / L sodium hydroxide solution and add it dropwise to water glass, stirring for 1 h;

[0052] Solution A was added dropwise to solution B and stirred for 2 hours. Finally, 11 mL of 2.92 mol / L potassium fluoride solution was added to adjust the pH to approximately 11.2. After stirring for 1 hour, a hydrothermal crystallization reaction was carried out at 230℃ for 72 hours. The product was removed, washed, dried, and calcined at 450℃ for 5 hours to obtain hierarchical porous ETS-10 zeolite. SEM observation showed that the product morphology was a nanocrystalline stacked morphology.

[0053] Example 4

[0054] In this case, the raw materials were added according to the following molar ratio: SiO2:TiO2:K2O:Na2O:AC:H2O = 6.2:1.0:1.8:4.5:0.8:185.

[0055] Solution A: Prepared by adding 6 mL of 1.51 mol / L citric acid solution dropwise to 10 mL of TiCl3;

[0056] Solution B: Measure 10 mL of 5.84 mol / L sodium hydroxide solution and add it dropwise to water glass, stirring for 1 h;

[0057] Solution A was added dropwise to solution B and stirred for 2 hours. Finally, 11 mL of 2.92 mol / L potassium fluoride solution was added to adjust the pH to approximately 11.2. After stirring for 1 hour, a hydrothermal crystallization reaction was carried out at 230℃ for 72 hours. The product was removed, washed, dried, and calcined at 450℃ for 5 hours to obtain hierarchical porous ETS-10 zeolite. SEM observation showed that the product morphology was a nanocrystalline stacked morphology.

[0058] Experiments 1-4 were set up to compare the effect of different amounts of citric acid on the system. The XRD patterns of the obtained zeolites are shown in [reference needed]. Figure 1 The crystallinity and mesopore volume data are shown in Table 1. ETS-10 zeolite can be synthesized with an AC:TiO2 molar ratio between 0.2 and 0.4, but no mesopores are formed. Hierarchical porous ETS-10 zeolite can be synthesized with an AC:TiO2 molar ratio between 0.6 and 0.8, and the crystallinity difference is not significant. The highest crystallinity is achieved when the AC:TiO2 molar ratio is 0.8; therefore, the AC:TiO2 ratio of 0.8 in Example 3 is selected as the optimal ratio.

[0059] Example 5

[0060] In this case, the raw materials were added according to the following molar ratio: SiO2:TiO2:K2O:Na2O:AC:H2O = 6.2:1.0:1.8:4.5:0.6:180.

[0061] Solution A: Prepared by dissolving 1.43g of solid citric acid in 10mL of TiCl3;

[0062] Solution B: Measure 10 mL of 2.43 mol / L sodium hydroxide solution and add it dropwise to water glass, stirring for 1 h;

[0063] Solution A was added dropwise to solution B and stirred for 2 hours. Finally, 11 mL of 2.92 mol / L potassium fluoride solution was added to adjust the pH to approximately 11.2. After stirring for 1 hour, a hydrothermal crystallization reaction was carried out at 230℃ for 72 hours. The product was removed, washed, dried, and calcined at 450℃ for 5 hours to obtain hierarchical porous ETS-10 zeolite. SEM observation showed that the product morphology was a typical truncated bipyramidal morphology of ETS-10.

[0064] Experiments 3 and 5 were set up to compare the effects of different material addition methods on the synthesis of zeolite. The obtained XRD patterns are shown in [reference needed]. Figure 2 Crystallinity and mesopore volume are shown in Table 1. In Example 5, solid citric acid was added directly. However, the strong acidity of citric acid easily leads to a decrease in the overall pH of the mother liquor, which in turn leads to the formation of quartz and other impurity phases. In Example 3, citric acid was diluted with a certain amount of water before being mixed with the titanium source. This effectively limits the negative effect of excessive citric acid leading to increased acidity. At the same time, by adjusting the concentration of the citric acid solution, the final pH value of the mother liquor will have greater flexibility.

[0065] Example 6

[0066] In this case, the raw materials were added according to a molar ratio of SiO2:TiO2:K2O:Na2O:AC:H2O = 6.2:1.0:1.8:4.5:0.6:155. The implementation process in this case is the same as in Example 3, except that the added potassium fluoride solution was changed to 5.0 mL of 8.42 mol / L. The ETS-10 zeolite obtained in this case was observed by SEM to have a nanocrystalline aggregate morphology.

[0067] Example 7

[0068] In this case, the raw materials were added according to the molar ratio of SiO2:TiO2:K2O:Na2O:AC:H2O = 6.2:1.0:1.8:3.0:0.6:170. The implementation process was the same as in Example 3, except that the added potassium fluoride solution was changed to 7.92 mL of 5.16 mol / L. The ETS-10 zeolite obtained in this case was observed by SEM to have a nanocrystalline aggregate morphology.

[0069] Example 8

[0070] In this case, the raw materials were added according to a molar ratio of SiO2:TiO2:K2O:Na2O:AC:H2O = 6.2:1.0:1.8:4.5:0.6:200. The implementation process was the same as in Example 3, except that the added potassium fluoride solution was changed to 14.0 mL of 2.91 mol / L. The ETS-10 zeolite prepared in this case was observed by SEM to have a nanocrystalline aggregate morphology.

[0071] Example 9

[0072] In this case, the raw materials were added according to the molar ratio of SiO2:TiO2:K2O:Na2O:AC:H2O = 6.2:1.0:1.8:4.5:0.6:210. The implementation process was the same as in Example 3, except that the added potassium fluoride solution was changed to 16.1 mL of 2.54 mol / L. The ETS-10 zeolite prepared in this case was observed by SEM to have a nanocrystalline aggregate morphology.

[0073] Experiments 3 and 6-9 were set up to compare the effects of different water-to-titanium ratios and system pH on the synthesis. The obtained XRD patterns are shown in [reference needed]. Figure 3 Crystallinity and mesopore volume are shown in Table 1. A water-to-titanium molar ratio of 185-200 can synthesize highly crystalline ETS-10 zeolite. When the water-to-titanium molar ratio is between 155-170, the system viscosity is high, easily leading to uneven mixing of inorganic species; furthermore, the higher system pH easily leads to the formation of the ETS-4 impurity phase. When the water-to-titanium ratio is greater than 200, the decreased system pH also induces the formation of impurities such as quartz and AM-1. Therefore, the optimal water-to-titanium molar ratio is 180-200.

[0074] Example 10

[0075] In this case, the raw materials were added according to the following molar ratio: SiO2:TiO2:K2O:Na2O:AC:H2O = 6.2:1.0:1.8:4.5:0.6:185.

[0076] Solution A: Prepared by adding 5 mL of 1.36 mol / L citric acid solution dropwise to 10 mL of TiCl3;

[0077] Solution B: Measure 10 mL of 2.43 mol / L sodium hydroxide solution and add it dropwise to water glass, stirring for 1 h;

[0078] 11 mL of 2.92 mol / L potassium fluoride solution was added to solution B to adjust the pH to approximately 11.2. The mixture was stirred for 1 h. Subsequently, solution A was added dropwise to the aforementioned system, and the mixture was stirred for 2 h. Finally, a hydrothermal crystallization reaction was carried out at 230 °C for 72 h. The product was then removed, washed, dried, and calcined at 450 °C for 5 h. SEM observation showed that the product morphology exhibited a nanocrystalline aggregate morphology on the surface. The results are as follows. Figure 7 and Figure 8 As shown.

[0079] Example 11

[0080] In this case, the raw materials were added according to the following molar ratio: SiO2:TiO2:K2O:Na2O:AC:H2O = 6.2:1.0:1.8:3.0:0.6:185.

[0081] 10 mL of 2.43 mol / L sodium hydroxide solution was added dropwise to water glass and stirred for 1 h. Then, 10 mL of TiCl3 solution was added dropwise to the system and stirred for 2 h. Next, 11 mL of 2.92 mol / L potassium fluoride solution was added and stirred for 1 h. Finally, 5 mL of 1.36 mol / L citric acid solution was added to adjust the pH to approximately 11.2. The mixture was then subjected to hydrothermal crystallization at 230 °C for 72 h. The product was collected, washed, dried, and calcined at 450 °C for 5 h. SEM observation revealed a smooth surface and a typical ETS-10 truncated bipyramidal morphology. The results are as follows: Figure 6 As shown.

[0082] Experiments 3, 10, and 11 were designed to compare the effect of different citric acid addition orders on the synthesis process. The obtained XRD patterns are shown in [reference needed]. Figure 4 Crystallinity and mesopore volume are shown in Table 1. In Example 10, only the order of addition of solution A and potassium fluoride was changed; the synthesized ETS-10 zeolites all exhibited mesopore formation, and the morphology was all nanocrystalline aggregates. SEM scan images are shown below. Figure 7 , Figure 8 The only difference between the two is their crystallinity. In Example 11, when the citric acid solution was added directly to the system without mixing with TiCl3, ETS-10 could be synthesized, but the morphology was a smooth, uniform tetragonal structure, and no mesoporous structures were formed. (SEM scan image shown). Figure 6 .

[0083] Example 12

[0084] In this case, the raw materials were added according to the following molar ratio: SiO2:TiO2:K2O:Na2O:AC:H2O = 6.2:1.0:1.8:4.5:0.6:185.

[0085] Solution A: Prepared by adding 5 mL of 1.36 mol / L citric acid solution dropwise to 10 mL of TiCl3;

[0086] Solution B: Measure 10 mL of 2.43 mol / L sodium hydroxide solution and add it dropwise to water glass, stirring for 1 h;

[0087] Solution A was added dropwise to solution B and stirred for 2 hours. Finally, 11 mL of 2.92 mol / L potassium fluoride solution was added to adjust the pH to approximately 11.2. After stirring for 1 hour, a hydrothermal crystallization reaction was carried out at 230℃ for 48 hours. The product was removed, washed, dried, and calcined at 450℃ for 5 hours to obtain hierarchical porous ETS-10 zeolite. SEM observation showed that the product morphology was a nanocrystalline stacked morphology.

[0088] Example 13

[0089] This case study follows the same molar ratio and implementation process as Example 3, except that the crystallization time is changed to 24 hours. The ETS-10 zeolite obtained in this case was observed to have a nanocrystalline aggregate morphology by SEM.

[0090] Example 14

[0091] This case study follows the same molar ratio and implementation process as Example 3, except that the crystallization time is changed to 12 hours. The ETS-10 zeolite obtained in this case was observed to have an amorphous morphology by SEM.

[0092] Example 15

[0093] This case study follows the same molar ratio and implementation process as Example 3, except that the crystallization time is changed to 6 hours. The ETS-10 zeolite obtained in this case was observed to have an amorphous morphology using SEM.

[0094] Comparative Example 1

[0095] This case study describes the preparation of a traditional microporous ETS-10 zeolite molecular sieve. The raw materials were added in a molar ratio of SiO2:TiO2:K2O:Na2O:H2O = 7.0:1.0:1.9:4.0:163.

[0096] 1.8 g of potassium fluoride was dissolved in 5 mL of H₂O to form solution C; 1.45 g of sodium hydroxide was dissolved in 10 mL of water and added dropwise to 9.2 mL of water glass. After stirring for 10 min, 5.9 g of TiCl₃ was added dropwise and stirred for 60 min. Then, solution C was added dropwise. After stirring for 2 h, the mixture was placed in a hydrothermal reactor and sealed. It was then crystallized in an oven at 230 °C for 48 h. The product was removed, washed, dried, and calcined at 450 °C for 5 h to obtain ETS-10 zeolite. SEM observation showed that its morphology was amorphous.

[0097] Experimental Examples 3, Examples 12-15, and Comparative Example 1 were set up to compare the effect of different crystallization times on the synthesis of ETS-10. The obtained XRD patterns are shown in [reference needed]. Figure 5Crystallinity and mesopore volume are shown in Table 1. In the initial stage of the hydrothermal reaction, the peak intensity of the characteristic peaks of the sample continuously increased with the extension of crystallization time, and the BET value and pore volume also increased. After 24 hours of crystallization, the characteristic peaks were basically complete, and the BET value was relatively stable. After 48 hours, the obtained sample had a high crystallinity, and the micropore volume was less than 0.10 cm³. 3 / g and 0.11cm 3 The volume fluctuates between / g and 0.15cm³, with mesoporous pore volume between 0.15 3 / g and 0.16cm 3 The values ​​fluctuated between / g. The texture properties of the two samples with crystallization times of 72h and 48h were almost identical, indicating that the crystallization time of the hierarchical porous ETS-10 zeolite with nanocrystalline stacking morphology prepared by this method can be shortened to 48h. In addition, Comparative Example 1 with a crystallization time of 48h did not have complete characteristic peaks.

[0098] Comparative Example 2

[0099] This case study demonstrates the preparation of hierarchical porous ETS-10 zeolite using the soft template method. The raw materials were added in a molar ratio of SiO2:TiO2:K2O:Na2O:H2O = 7.0:1.0:1.9:4.0:163.

[0100] 1.8g of potassium fluoride is dissolved in 5mL of H2O to form solution A;

[0101] Dissolve 1.45g of sodium hydroxide in 10mL of water, add it dropwise to 9.2mL of water glass, stir for 10min, then add 5.9g of TiCl3 dropwise, stir for 60min, then add solution A dropwise; stir for 2h, then add 4.0mL of LTPOAB.

[0102] The product was then placed in a hydrothermal reactor and sealed, and crystallized in an oven at 230°C for 72 hours. After the product was removed, it was washed, dried, and calcined at 450°C for 5 hours to obtain ETS-10 zeolite. SEM observation showed that its morphology was a typical truncated bipyramidal morphology of ETS-10.

[0103] Comparative Example 3

[0104] Preparation of ETS-10 zeolite molecular sieve with sodium lignosulfonate as additive. In this case, the raw materials were added according to the following molar ratio: Na2O:K2O:TiO2:SiO2:IL-LnNa:H2O = 3.5:1.6:1.0:5.5:0.043:181.

[0105] Take 16 mL of water glass and stir at room temperature for 10 min, then mix thoroughly with 2 mL of 1 L-LnNa (sodium lignosulfonate modified with 1-ethyl-3-methylimidazolium chloride) solution. After stirring for 1 h, add 20 mL of H2O and continue stirring for 20 min. Then add 6.9 g of NaCl and 2.8 g of KF and stir for 1 h each. Finally, add 1.3 g of P25 and stir for 2 h. Then, put it into a hydrothermal reactor and seal it. Let it stand in an oven at 230 ℃ for 60 h to crystallize. After taking out the product, wash and dry it, and calcine it at 450 ℃ for 5 h to obtain ETS-10 zeolite. SEM observation showed that its morphology was cauliflower-shaped.

[0106] The product preparation process parameters and product properties of the above embodiments and comparative examples are shown in Table 1.

[0107] Table 1. Preparation process parameters and properties of the products of the examples and comparative examples.

[0108]

[0109]

[0110] Application Example 1

[0111] The multi-level porous ETS-10 zeolite molecular sieves of Examples 3, 7, 10, 11, 12 and Comparative Examples 1-3 were applied to the CO2 carbonylation of alcohols, specifically in the reaction of CO2 carbonylation of glycerol to prepare glycerol carbonate.

[0112] The ETS-10 zeolite molecular sieve prepared in the above case was used as a support to support transition metals to prepare a catalyst. The specific preparation process is as follows:

[0113] The ETS-10 zeolite samples prepared in the above cases were used as catalyst supports, and metal species were introduced at 5 wt% of the support mass via an equal-volume impregnation method. The precursor of the metal species was nitrate, and zinc nitrate hexahydrate was selected in this example. The impregnated samples were dried in air at room temperature overnight, then dried in an oven at 110℃, and finally calcined at 450℃ for 4 hours.

[0114] The catalytic reaction was carried out in a 250 mL high-pressure reactor. 0.25 g of the prepared catalyst powder and 1.2 g of glycerol were weighed and added to a 200 mL high-pressure reactor, followed by 4 g of 2-cyanopyridine as a dehydrating agent and 1 mL of tetraethylene glycol as an internal standard. CO2 was repeatedly purged three times to remove excess air from the reactor, and then 4 MPa of CO2 was introduced. The reaction conditions were: reaction temperature 150 °C, reaction time 6 h, and stirring speed 600 rpm during the reaction. After the reaction was completed, the pressure was released, the product was diluted with ethanol, and the product was quantified using gas chromatography.

[0115] The catalytic activity of the catalyst was evaluated by the carbon dioxide conversion rate and product yield, and the results are shown in Table 2.

[0116] Table 2 Comparison of CO2 carbonylation glycerol activity on different catalysts

[0117] Example 3 Carrier-Zn 47.5 37.0 Example 7 Carrier-Zn 46.3 29.5 Example 10 Carrier-Zn 47.3 30.7 Example 11 Carrier-Zn 37.5 23.5 Example 12 Carrier-Zn 48.1 37.4 Comparative Example 1: Carrier-Zn 30.8 20.9 Comparative Example 2: Carrier-Zn 44.2 30.3 Comparative Example 3: Carrier-Zn 39.6 28.7 <![CDATA[CeO2]]> 42.0 18.7 <![CDATA[CeO2-ZrO2]]> 40.9 36.3

[0118] It is evident that the transition metal catalyst prepared using hierarchical porous ETS-10 with 90% crystallinity and a nanocrystalline stacking morphology as a support exhibits a conversion rate greater than 47% and a glycerol carbonate yield greater than 30% in the catalytic reaction of CO2 carbonylation of glycerol to glycerol carbonate. In contrast, the transition metal catalyst prepared using ETS-10 with 83.03% crystallinity (Example 7) or a typical truncated bipyramidal morphology (Example 11) as a support exhibits a conversion rate less than 46.5% and a glycerol carbonate yield less than 30% in the catalytic reaction of CO2 carbonylation of glycerol to glycerol carbonate.

[0119] Furthermore, compared to the performance of catalysts prepared using Comparative Examples 1, 2, and 3 as supports, and the performance of CeO2-ZrO2 mixed oxide catalysts described in the literature, the hierarchical porous ETS-10 with crystallinity of over 90% and nanocrystalline stacking morphology prepared by this invention exhibits superior catalytic performance.

[0120] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing ETS-10 zeolite with a nanocrystalline stacked morphology, characterized in that, Includes the following steps: Solution A is obtained by separately preparing solutions of citric acid and titanium trichloride and then mixing them thoroughly. Sodium hydroxide solution was added to water glass and stirred until homogeneous to obtain solution B. After adding solution A dropwise to solution B, potassium fluoride solution is added to adjust the pH of the system to 11-11.

5. Alternatively, potassium fluoride solution is added dropwise to solution B first to adjust the pH of the system to 11-11.5 before adding solution A. The mixture is stirred continuously and subjected to a hydrothermal crystallization reaction at 230°C for 48-72 hours. The product is then removed, washed, dried, and calcined at 450°C for 5 hours to obtain ETS-10 zeolite with a nanocrystalline morphology. The raw materials are added according to the following molar ratio: SiO2:TiO2:K2O:Na2O:citric acid:H2O=6.2:1.0:1.8:4.5:(0.5-0.8):(185-200).

2. The method for preparing ETS-10 zeolite with a nanocrystalline stacked morphology according to claim 1, characterized in that, Raw materials should be added according to the following molar ratio: SiO2:TiO2:K2O:Na2O:citric acid:H2O=6.2:1.0:1.8:4.5:(0.6-0.8):

185.

3. The method for preparing ETS-10 zeolite with a nanocrystalline stacked morphology according to claim 1, characterized in that, The system should be stirred for 1-2 hours before adding the potassium fluoride solution and after adjusting the pH of the system to the required value.

4. The application of ETS-10 zeolite with a nanocrystalline stacked morphology in the catalytic CO2 carbonylation of alcohols, characterized in that, The ETS-10 zeolite with a nanocrystalline stacking morphology prepared according to any one of claims 1-3 is used as a support to support transition metals to prepare a catalyst.

5. The application according to claim 4, characterized in that, The transition metal is one or more of zinc, cobalt, nickel, cerium, and zirconium.

Citation Information

Patent Citations

  • Titanium silicalite molecular sieve and synthetic method

    CN104724721A

  • Preparation method of ETS-10 molecular sieve

    CN107601520A

  • Template-agent-free hierarchical pore ETS-10 zeolite molecular sieve as well as synthesis method and application thereof

    CN117566755A